Enhancing Motivation to Learn Mathematics Among Elementary School Children at Pondok X - Duarsa, Naraya Kinastrian Siniddhikara; Ismana, Arsy Febrianti Putri; Azzuhruf, Naura Reisya; Wibowo, Astri Anggraini Hapsari (CV. Publikasi Indonesia, 2025)
This research aimed to enhance the motivation of elementary school children aged 7-11 years at Pondok X in learning Mathematics through interactive and engaging methods. The research employed a pre-test and post-test design, with a learning motivation questionnaire encompassing six key indicators: (1) desire to succeed, (2) learning drive, (3) future expectations, (4) recognition in learning, (5) interest in learning activities, and (6) a conducive learning environment. The results showed a notable increase in motivation, particularly in the areas of desire to succeed, internal learning drive, and future aspirations. The interventions, including educational games such as